Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/15332640.2011.573315
|View full text |Cite
|
Sign up to set email alerts
|

Academics and Substance Use among Latino Adolescents: Results from a National Study

Abstract: This study investigated the relationship between academic factors and past-year alcohol, cigarette, and marijuana use in an adolescent sample of Latinos. Secondary data analysis was conducted using a subsample of Latino adolescents (N=2,593) from the 2006 National Survey on Drug Use and Health. School connectedness and parental involvement in school were protective across all substances. Fighting in school increased the risk for use of all substances, and failing grades increased the risk for alcohol and marij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…School enjoyment (i.e., the degree to which the student likes going to school, attending classes, and feels positively linked to the school) has been found to serve as a protective factor against substance use for many adolescent groups (Bryant, Schulenberg, O'Malley, Bachman, & Johnston, 2003;Shears et al, 2006;Vaughan, Kratz, & d'Argent, 2011;Wang, Matthew, Bellamy, & James, 2005), including Latinos=as (Prado et al, 2009). School enjoyment has been found to be more protective for adolescents living in more rurally isolated areas than those living in more populated areas (Shears et al, 2006).…”
Section: School Influencesmentioning
confidence: 94%
See 2 more Smart Citations
“…School enjoyment (i.e., the degree to which the student likes going to school, attending classes, and feels positively linked to the school) has been found to serve as a protective factor against substance use for many adolescent groups (Bryant, Schulenberg, O'Malley, Bachman, & Johnston, 2003;Shears et al, 2006;Vaughan, Kratz, & d'Argent, 2011;Wang, Matthew, Bellamy, & James, 2005), including Latinos=as (Prado et al, 2009). School enjoyment has been found to be more protective for adolescents living in more rurally isolated areas than those living in more populated areas (Shears et al, 2006).…”
Section: School Influencesmentioning
confidence: 94%
“…School achievement and higher grades during adolescence have been correlated with less substance use later in life (Bryant et al,, 2003). Among Latino=a adolescents, failing grades are a predictor of alcohol and marijuana use (Vaughan et al, 2011). Both parental (Vaughan et al, 2011) and adolescent (Farb & Matjasko, 2012) school involvement have been found to be negatively associated with substance use.…”
Section: School Influencesmentioning
confidence: 96%
See 1 more Smart Citation
“…Schools are one of the primary developmental contexts for adolescents and play an important role in risk and protective factors for alcohol and other substance use. The current study adds to what is known about the role that school environment plays in alcohol use among Latino youth (e.g., Prado et al, 2009;Vaughan et al, 2011) specifically by testing nativity as a moderator of the associations between school factors and alcohol use. Further, this study focuses on alcohol use given that Latino 8 th graders, when compared to their White and African American counterparts, report the highest rates of past 30 day alcohol use, drinking to intoxication, and drinking 5 or more drinks in the past two weeks (Johnston et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…An adolescent's interaction with their school environment can impact their academic achievement as well as their alcohol and drug use behaviors (Catalano et al, 2011;Prado et al, 2009;Vaughan, Kratz, & d' Argent, 2011;Wang, Matthew, Bellamy, & James, 2005). One Add Health study of school connectedness defined the construct as the degree to which students feel they are a part of their school (i.e., sense of belonging), feel they are close to others at school, and are treated fairly by teachers and peers (Prado et al, 2009).…”
mentioning
confidence: 98%